Implementation of the IMTAQ Development Program in Improving Akhlaqul Karimah Student MI Al-Ihsan IIA Larangan Perreng Pragaan Sumenep - Ach. Barizi Khalili; Achmad Maulidi (Penerbit Hellow Pustaka, 2024)
MI Al-Ihsan Iia Student Delinquency Behavior for the Prant Sumenep Perreng Prantan has resisted the teacher when the teacher gives motivation because some students and their students are quarrels. In this case the importance of implementing the IMTAQ coaching program in growing student morality so that the researcher is interested in examining the implementation of the IMTAQ Development Program in fostering student morality. The study aims to find out how the implementation of the IMTAQ coaching program in the case of the student's morality at MI Al-Ihsan IIA and what are the inhibiting and supporting factors in the implementation of the IMTAQ Development Program in strengthening the student morality at MI Al-Ihsan IIA. Researchers use descriptive qualitative research using the observation method at MI Al-Ihsan IIA, interviews with school principals and Islamic religious education teachers and documentation of school activities which are then analyzed to obtain data or information. This thesis produces the conclusion that in the implementation of the IMTAQ coaching program in strengthening the student morality at MI Al-Ihsan IIA, namely giving role models, teachers in educating students have a clear vision, upholding student discipline in the teaching and learning process (KBM) and also their concern for the environment . As for the inhibiting and supporting factors of PAI teachers in the implementation of the IMTAQ coaching program in the case of the student morality at MI Al-Ihsan IIA, namely the collaboration of the MI Al-Ihsan IIA teacher with parents, the awareness and will of the students themselves, the creation of a conducive environment , students pray in congregation every day. The teacher inhibiting factors are, the lack of teacher awareness in guiding it, lack of student awareness and interest, lack of guidance for parents and the surrounding environment.